Solutions From Cooked Beans as Soil Organic Matter and Water Provider: Case Study of Ferralitic Soils From the Centre Region of Cameroon - TUEBUE, J.C. FOPOUSSI; TCHINDA, I.N. (European Journal of Applied Sciences, 2021)
The purpose of this study is to evaluate the bean end-cooking solution as a provider of organic matter and water for soils. To do this, ferralitic soils from the Central Region of Cameroon were selected. The work took place from the middle to the end of the dry season. The field work consisted on soils description, watering the soils with the bean end-cooking solution and water from a well with known chemical characteristics, and the sampling of the arable part of soils, as well as the acquisition of bean (Phaseolus vulgaris L.). In the laboratory, it was a question of producing the end-of-cooking solution for the bean, analyzing the samples of soils, witnesses, sprayed with water from a domestic well, and with the end-of-cooking solution of the bean. The analysis focused on organic carbon, total nitrogen, and the weight water content (TEP). In the arable part of the control, the organic carbon content is 1.42% for an organic matter content of 2.85%; the total nitrogen content is 0.251%, the weight water content is 18%. In the arable part of soils sprinkled with water from the domestic well, the organic carbon content is 1.45% for an organic matter content of 2.9%; the total nitrogen content is 0.251%, the weight water content is 21.5%. In the arable part of soils sprinkled with the bean end-cooking solution, the organic carbon content is 2.01% for an organic matter content of 4.02%; the total nitrogen content is 0.365%; the weight water content is 31%. In the arable part of soils sprinkled with the solution at the end of cooking the beans and then mounded, the organic carbon content is 2.5% for an organic matter content of 5%; the total nitrogen content is 0.39%; the weight water content is 33%. The ridging of the surfaces having received water from the end of cooking the bean has canceled the emanation of odors in contrast to what was raised with the surfaces which received the end of cooking solution of the bean without ridging. Thus, like human urine, the water from the end of cooking the beans is presented as a complete fertilizer. The ridging after the application of the bean end-of-cooking solution maximizes the positive effects of the said solution.